Beer choice and consumption determinants when craft beers are tasted: An exploratory study of consumer preferences. (April 2015) - Aquilani, Barbara; Laureti, Tiziana; Poponi, Stefano; Secondi, Luca
Highlights: Craft beer is a rapidly growing segment of the beverage industry. The profile of commercial beer drinkers who have tasted craft beer was analyzed. Habits and consumption occasions affect the probability of tasting craft beer. The environment in which the beer is consumed influences craft beer choice. The success of craft beer is due to the so-called "taste revolution". Abstract: The aim of this paper is to study the emerging craft beer industry from a consumer preference perspective. The craft beer industry is one of the growing segments in the beverage industry and its increasing popularity also affects individuals' commercial beer preferences and consumption trends, although no empirical study has yet been carried out in Europe on this topic. Our exploratory study is aimed at comparing the "purely" commercial beer consumer profile with that of commercial beer consumers who have already tasted craft beers. It was observed that aroma and perceived quality, as well as the preference for draft beer, drinking beer frequently or by oneself are all factors that explain the propensity of "purely" commercial beer drinkers to taste craft beer. It was also found that beer consumers' evaluations of characteristics and brands differed depending on whether they had previously tasted craft beer or not. Moreover, craft beer is chosen according to different flavor preferences compared to commercial beer, it is mainly drunk by frequent beer drinkers in pubs and with family members and it is perceived to be of higher quality than commercial beer due to the raw materials used for brewing and its overall quality. These results can help both new entrepreneurs in the craft beer segment as well as big manufacturing firms in trying to better understand this new consumption trend in order to meet the new needs and preferences of beer consumers.